2015
DOI: 10.1108/pr-12-2012-0209
|View full text |Cite
|
Sign up to set email alerts
|

Explaining the black box: HPWS and organisational climate

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(49 citation statements)
references
References 67 publications
1
45
0
3
Order By: Relevance
“…Third, by showing that the WRC is one of the mechanisms through which leadership can influence the commitment of unionised workers, our study empirically demonstrates previous propositions regarding the intervening role of the WRC (Cafferkey & Dundon, ; Dastmalchian, ; Pyman et al, ). As such, immediate supervisors who display transformational leadership will foster organisational commitment among workers, by contributing to develop a WRC based on mutual recognition and trust within their organisation.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Third, by showing that the WRC is one of the mechanisms through which leadership can influence the commitment of unionised workers, our study empirically demonstrates previous propositions regarding the intervening role of the WRC (Cafferkey & Dundon, ; Dastmalchian, ; Pyman et al, ). As such, immediate supervisors who display transformational leadership will foster organisational commitment among workers, by contributing to develop a WRC based on mutual recognition and trust within their organisation.…”
Section: Discussionsupporting
confidence: 76%
“…In this sense, union and management first‐line representatives, through their daily interactions with workers, can influence workers' commitment toward their union and organisation by becoming a significant source of information on the nature of the WRC in their organisation. A number of authors (e.g., Cafferkey & Dundon, ; Dastmalchian, ; Gordon & Ladd, ; Pyman et al, ) have proposed that understanding workers' interpretation of their WRC allows for a better comprehension of their attitudinal reactions, such as their sense of commitment. This reasoning has led these authors to consider the WRC as an important intervening variable between institutional and relational factors, such as union and management leadership, and workers' attitudes and behaviours in unionised settings.…”
Section: Literature and Hypothesismentioning
confidence: 99%
“…One major concern in workplace partnership debates is the underlying mechanisms through which mutual gains for all stakeholders might be delivered (Wilkinson et al , ). The employment relations climate holds great promise of being a useful mediator through which partnership gains might be accumulated (Redman and Snape, ; Cafferkey and Dundon, ). In fact, some studies have shown qualitative evidence that hints that a positive employment relations climate may mediate the relationship between workplace partnership and desirable employee outcomes (Bélanger and Edwards, ; Geary, ; Glover et al , ).…”
Section: Mutual Gains Perspectivementioning
confidence: 99%
“…In particular, there is an identified deficit of sector specific studies incorporating multilevel respondents (Cafferkey and Dundon 2015). While there have been some qualitative studies on people management processes in Irish hospitals (e.g.…”
Section: The Research Contextmentioning
confidence: 99%